1992
DOI: 10.1007/bf01270572
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic and docosahexaenoic acids in cultured rat ventricular myocytes and hypoxia-induced alterations of phospholipase?A activity

Abstract: Hypoxia was reported to induce a decrease in phosphatidylcholine-hydrolyzing phospholipase activity (PC-PLA) in cultured rat cardiomyocytes. This work was intended to compare the influence of the presence of either eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) in the phospholipids on the PC-PLA activity in normoxic and hypoxic conditions. The enrichment of the medium with EPA or DHA resulted in cell phospholipids containing about 2% or 22% DHA, respectively. These cells were then submitted for 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The cells were grown in a standard culture medium [Ham's FI0 (Seromed Biochrom, Berlin, Germany) medium supplemented with 10% fetal calf serum and 10% human serum] in a humidified atmosphere at 37~ containing 5% CO 2. After 24 h, the cells were incubated for four days in the same medium supplemented as serum albumin-bound fatty acids with either 20:5n-3 (EPA) or 22:6n-3 (DHA), which led to two populations (EPA and DHA cells) from the same cell pool (23).…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…The cells were grown in a standard culture medium [Ham's FI0 (Seromed Biochrom, Berlin, Germany) medium supplemented with 10% fetal calf serum and 10% human serum] in a humidified atmosphere at 37~ containing 5% CO 2. After 24 h, the cells were incubated for four days in the same medium supplemented as serum albumin-bound fatty acids with either 20:5n-3 (EPA) or 22:6n-3 (DHA), which led to two populations (EPA and DHA cells) from the same cell pool (23).…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…However, the change of fatty acid composition of cardiomyocytes membrane can also affect the behavior of receptors as well as of transporters and enzymes inserted in the lipid layer. It was shown that cardiomyocytes membrane fluidity was increased following addition of DHA, EPA and ALA (15) and that the type of the long chain omega-3 PUFAs in the phospholipids played a role in the regulation of phosphatidylcholine-hydrolyzing phospholipase activity (31). Activation of the PKA pathway by EPA administration on rat ventricular myocytes was also proved.…”
Section: In Vitro Effects Of Omega-3 Pufas On Cardiac Myocytes: Evidementioning
confidence: 99%